Development of Guided Inquiry-Oriented Electronic Student Worksheets to Improve Students Metacognitive Skills on Chemical Equlibirum Material - Laili, Balinda Ayu; Azizah, Utiya (Asian Journal of Science Education, 2024)
Metacognitive skills are important to train students in developing and improving 21st century skills. One of the efforts to train metacognitive skills in students by using relevant learning media, namely guided inquiry-oriented electronic student worksheets. This research aims to determine the feasibility of developing a guided-inquiry-oriented student e-worksheet to improve metacognitive skills on chemical equilibrium. The feasible to use, in terms of validity, practicality, and effectiveness. The method uses in this research is RD with a 4D model, but only reached the develop. The subjects of this studi amounted to 20 student of class XI-1 state senior high school of 21 Surabaya. This results obtained are that the student e-worksheet developed is feasible because the validity results the content and construct in mode 5 with a very valid category. The practicality results obtained a student response questionnaire of 95,29% in the very practical category and supported by the results of observations of student activities obtained a percentage of 92,78% in the very practical category. The effectiveness results was obtained from the pretest dan possttest results, which analyzed using the SPSS Paired Sample t-Test, the results showed that there was an increase in students metacognitivse skills, namely with a sig. value (two-sided p) 0.001.